EDUKASI KELAS IBU HAMIL SEBAGAI UPAYA PENINGKATAN PENGETAHUAN 10 T - Suhayati; Ika Kania Fatdo Wardani; Rosi Kurnia Sugiharti; Rohani Siregar (JOMIS (Journal of Midwifery Science), 2026)
West Java Health Office in 2024 recorded 749 cases of maternal deaths, with Bekasi Regency reporting 46 cases. One of the efforts to reduce AKI is to improve the quality of integrated antenatal care (ANC) services through the implementation of the 10T pregnancy examination standard. This study aims to analyze the influence of education in pregnant women's classes on increasing knowledge about the 10T ANC examination. The research uses a quasi-experimental design with a one group pretest–posttest approach. The research sample was 30 pregnant women taken by total sampling technique. The intervention was in the form of health education using video media, while knowledge measurement was carried out through questionnaires. The data collection will be carried out in July 2025 in Mangunjaya Village, Bekasi Regency. Data analysis used frequency distribution and Wilcoxon test. The results showed that as many as 25 respondents (83.3%) experienced an increase in knowledge after being given education, with a mean rank value of 16.38. The Wilcoxon test showed a value of p = 0.000 (p < 0.05), which indicates a significant influence of education on pregnant women's knowledge about the 10T ANC examination. Classroom education for pregnant women has been shown to be effective in increasing knowledge, which is expected to support healthy behaviors during pregnancy, increase awareness of red flags, and reduce the risk of complications. It is necessary to strengthen health education in a sustainable manner by health workers to improve the quality of ANC services